Knowledge and Misconceptions about Malaria among Pregnant Women in a Post-Conflict Internally Displaced Persons' Camps in Gulu District, Northern Uganda - Obol, James (SAGE-Hindawi Access to Research, 2011)
Background. In Uganda Malaria continues to be a major public health problem accounting for about 30–50% of all outpatient consultations and 35% of hospital admissions and a leading cause of mortality and morbidity. Pregnant women and their unborn children are vulnerable to malaria. Methods. A cross-sectional survey was conducted in 20 postconflict IDP camps of Gulu district selected randomly as clusters. 769 pregnant women were interviewed. Results. The majority of the respondents 85% have ever heard about malaria. Most (80%) 571 respondent attributed malaria to be transmitted by mosquito bites, 15 said cold weather, 53 said dirt, and 35 said not sleeping under net. Most (91%) 683 respondents mentioned that malaria was caused by mosquito, 28 mentioned cold food, 3 mentioned playing in the rain, 19 mentioned cold weather, and 6 mentioned eating mangos. Conclusion. Most pregnant women in the post conflict IDP camps have relatively high knowledge about malaria transmission, signs, symptoms, and consequences during pregnancy. However, majority of respondents had misconception about the cause of malaria while a few had misconception about the mode of malaria transmission.